(3GdCUhd dGbdjOSs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3Cf Gbd GdGYOGO Ydi bSeI s
(3BNQgG (B:s
(3Cbd YOO ef hPdc eG GQOfG Cf fHjf s
(3GdfSNI HgG MhGTs
(3cJHJ HNW bdjd GdfbWs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
Keywords: (3GdWHs